The Influence of Satisfaction, Compensation, and Communication on Loyalty of Honorary Employees at the Class 2 Railway Engineering Center for Northern Sumatra Region - Pitriani Lubis; Rusiadi; Bachtiar Effendi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The goal of this research was to examine the influence of satisfaction, compensation, and communication on the loyalty of honorary workers at the Class 2 Railway Engineering Center in the Northern Sumatra Region. This research examined a population of 71 honorary workers. The sample size was decided by the response rate, which reached 71 temporary workers. The data collection technique used was saturated sampling. Primary data was acquired using surveys and then analyzed using the SPSS Version 24 program. The research was conducted in 2022. The study made use of several linear regression models. The results suggested that, either partly or concurrently, satisfaction, reward, and communication all had a favorable and substantial influence on the loyalty of honorary workers at the Class 2 Railway Engineering Center for the Northern Sumatra Region. The satisfaction variable, which had the highest tally of 5.261, had the strongest effect on employee loyalty. Furthermore, satisfaction, compensation, and communication can explain and achieve 93.4 percent of employee loyalty, with the remaining 93.4 percent explained by other variables. Employee loyalty was shown to be integrally tied to work satisfaction, compensation, and communication.